Innovation of a composter to treat a domestic waste - Asti Mulasari Surahma; Sulistyawati Sulistyawati; Wahyuni Sukesi Tri; Tentama Fatwa (BIO Web of Conferences)
Waste treatment is very important practise in a country which have high population number, such as Indonesia. Otherwise, there will be overwhelming garbage, which possibly leads to environmental and health problems. However, many people in society still have a low awareness of waste management. The complexity of managing waste is still considered not comparable to the benefits obtained. Therefore, it is necessary to offer the alternative on waste management technologies that are environmentally friendly and in accordance with the needs and economic capabilities of the community. Aims: to develop a Composter to treat a household waste in effective and safe for the community. Methods: This research develops products by making prototypes. Experimental design was used on this research that began with laboratory tests for product and functions feasibility. An environmental health risk analysis was carried out to ensure that the product was safe for public health. Results: We produced a portable Composter for using in household level. This product passed the feasibility test, function feasibility test, and environmental health risks measurement. Conclusions: A household scale portable garbage bin be able to function as a composter tank and the environmental health risks was remains acceptable when the tool was operated.